Pengaruh Konservatisme Akuntansi, Inventory Intensity, dan Sales Growth terhadap Praktik Tax Avoidance pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Periode 2020-2024 - Fa’iz Rahadien Hafiz; Lintang Kurniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of accounting conservatism, inventory intensity, and sales growth on tax avoidance practices in Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative approach with a causal comparative (ex post facto) method. Secondary data in the form of annual financial statements are analyzed using multiple linear regression. The results indicate that, partially, accounting conservatism and sales growth do not have a significant effect on tax avoidance. In contrast, inventory intensity has a positive and significant effect on tax avoidance, indicating that a higher proportion of inventory in the asset structure increases the tendency of companies to engage in tax avoidance. Simultaneously, accounting conservatism, inventory intensity, and sales growth have a significant effect on tax avoidance. These findings imply that inventory management characteristics are a key determinant of tax avoidance practices in the property sector, while accounting conservatism and sales growth are not major determinants in the Indonesian taxation context during the study period.